Highly pathogenic avian influenza: pandemic preparedness for a scenario of high lethality with no vaccines - Possas, Cristina; Marques, Ernesto T. A.; Oliveira, Alessandra; Schumacher, Suzanne; Siqueira, Marilda M.; McCauley, John; Antunes, Adelaide; Homma, Akira (Frontiers in Public Health, 2025)
Highly Pathogenic Avian Influenza (HPAI) viruses, particularly H5N1 and H7N9, have long been considered potential pandemic threats, despite the absence of sustained human-to-human transmission. However, recent outbreaks in previously unaffected regions, such as Antarctica, suggest we may be shifting from theoretical risk to a more imminent threat. These viruses are no longer limited to avian populations. Their increasing appearance in mammals, including dairy cattle and domestic animals, raises the likelihood of viral reassortment and mutations that could trigger a human pandemic. If such a scenario unfolds, the world may face a crisis marked by high transmissibility and lethality, without effective vaccines readily available. Unlike the COVID-19 pandemic, when vaccines were rapidly developed despite inequities in access, the current influenza vaccine production model, largely reliant on slow, egg-based technologies, is insufficient for a fast-moving outbreak. While newer platforms show promise, they remain in early stages and cannot yet meet global demand, which alerts to the urgent need for accelerating vaccine and drug development, especially universal vaccines, next-generation vaccine platforms designed to provide broad, long-lasting protection against a wide spectrum of HPAI virus subtypes and strains. Here we propose a paradigmatic shift toward a more integrated, digitalized One Health surveillance system that links human, animal, and environmental data, especially in high-risk spillover regions. We underscore that Artificial Intelligence can revolutionize pandemic preparedness strategies, from improving early detection to speeding up vaccine and drug development and access to medical care, but should not be considered a stand-alone solution.